2020
DOI: 10.1007/s13596-020-00473-3
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical knowledge of medicinal plants used in the treatment of male infertility in southern Benin

Abstract: Infertility is a concern for couples, families and society. In almost half of the cases, it is due to male infertility. This infertility, in developing countries like Benin, often cured by the use of medicinal plants. This study aimed to enlist knowledge about medicinal plants used in the treatment of male infertility in southern Benin. An ethnomedicinal investigation has been conducted in southern Benin by questioning traditional healers and market herbalists using the method of semi-structured interview. Eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 100 publications
2
21
0
2
Order By: Relevance
“…In this present study, we aimed to investigate the effects and mechanisms of various plants extracts and natural products on the reproductive system. A large number of plants have been used to treat infertility for thousands years worldwide, including Korea [ 38 , 39 ]. Additionally, numerous natural products, including plant extracts were discovered to possess potential effects in reversing reproductive activity in both males and females.…”
Section: Plant Extract and Infertilitymentioning
confidence: 99%
“…In this present study, we aimed to investigate the effects and mechanisms of various plants extracts and natural products on the reproductive system. A large number of plants have been used to treat infertility for thousands years worldwide, including Korea [ 38 , 39 ]. Additionally, numerous natural products, including plant extracts were discovered to possess potential effects in reversing reproductive activity in both males and females.…”
Section: Plant Extract and Infertilitymentioning
confidence: 99%
“…Similar data have been reported by other authors in the same study area. 20,22,23 These results indicate that older people hold a large share of the traditional medicinal knowledge that is part of the oral tradition. Dougnon et al 35 reported that in Africa the medicinal knowledge of plants has an ancestral character and that it is the sages (older people) who hold the traditional knowledge…”
Section: Discussionmentioning
confidence: 95%
“…16,17 In Benin, the total Beninese flora is rich, with 2807 plant species, and according to Akoègninou et al 18 offers the possibility of using several plants in traditional medicine. For this purpose several ethnobotanical surveys have been conducted on the traditional treatment of various diseases in Benin [19][20][21][22][23] . However, in spite of this plurality of ethnomedical data available in the Beninese scientific literature, rare are the data that have mentioned the specific use of the 17 before mentioned plants in the traditional treatment of diarrhoea.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
See 1 more Smart Citation
“…Akoègninou et al [ 8 ] estimated the Beninese flora at more than 2807 plant species. Gardenia ternifolia ( G. ternifolia ), Cassytha filiformis ( C. filiformis ), and Rourea coccinea ( R. coccinea ) are three plants of Beninese flora used in the traditional treatment of male infertility [ 9 ]. Recent studies reported the antioxidant potential and the richness of these three plants in polyphenols and flavonoids, which often are responsible for their medicinal properties [ 10 ].…”
Section: Introductionmentioning
confidence: 99%